East on Sunset - Mercer, Ken, 1962- (New York : Minotaur Books, 2011)
Retiring from law enforcement to start a dream job and rekindle his marriage, former LAPD detective Will MacGowan is violently targeted by a recently released man he helped to send to prison and is forced to confront eye-opening realities from his past.
Keywords: Ex-police officers -- Fiction; Stalking victims -- Fiction; Mystery fiction